Adipose tissue remodeling in a novel domestic porcine model of diet‐induced obesity. (31st December 2014) - Pawar, Aditya S.; Zhu, Xiang‐Yang; Eirin, Alfonso; Tang, Hui; Jordan, Kyra L.; Woollard, John R.; Lerman, Amir; Lerman, Lilach O.
<x xml:space="preserve">Abstract</x> Objective To establish and characterize a novel domestic porcine model of obesity. Methods Fourteen domestic pigs were fed normal (lean, n = 7) or high‐fat/high‐fructose diet (obese, n = 7) for 16 weeks. Subcutaneous abdominal adipose tissue biopsies were obtained after 8, 12, and 16 weeks of diet, and pericardial adipose tissue after 16 weeks, for assessments of adipocyte size, fibrosis, and inflammation. Adipose tissue volume and cardiac function were studied with multidetector computed tomography, and oxygenation was studied with magnetic resonance imaging. Plasma lipids profile, insulin resistance, and markers of inflammation were evaluated. Results Compared with lean pigs, obese pigs had elevated cholesterol and triglyceride levels, blood pressure, and insulin resistance. Both abdominal and pericardial fat volume increased in obese pigs after 16 weeks. In abdominal subcutaneous adipose tissue, adipocyte size and both tumor necrosis factor (TNF)‐α expression progressively increased. Macrophage infiltration showed in both abdominal and pericardial adipose tissues. Circulating TNF‐α increased in obese pigs only at 16 weeks. Compared with lean pigs, obese pigs had similar global cardiac function, but myocardial perfusion and oxygenation were significantly impaired. Conclusions A high‐fat/high‐fructose diet induces in domestic pigs many characteristics of metabolic syndrome, which is useful for investigating the effects of the obesity.